Pengaruh Self-Reward dan Gaya Hidup terhadap Perilaku Konsumtif Mahasiswa dengan Kontrol Diri sebagai Variabel Moderasi - Maurheen Queena Hamada; Hwihanus Hwihanus (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This empirical study investigates the influence of self-reward and lifestyle on the consumptive behavior of university students, incorporating self-control as a moderating variable. Utilizing an explanatory quantitative approach, data were gathered from one hundred active undergraduate students in Malang through structured questionnaires and analyzed using moderated regression analysis. The findings reveal that both self-reward and lifestyle exert a positive and significant effect on student consumptive behavior, driven largely by digital marketing exposure and social conformity. Furthermore, self-control acts as a pure moderator that significantly mitigates the positive relationship between these predictors and consumptive habits. These results highlight that strengthening students internal regulatory mechanisms is crucial for mitigating excessive spending tendencies and fostering sustainable financial management in higher education